Magnetohydrodynamic Flow Past a Sphere - Swarup, S.; Sinha, P.C. (Engineering Transactions, 1977)
This paper deals with the slow steady flow of an incompressible, viscous, electrically-conducting fluid past a sphere in the presence of a uniform magnetic field. The magnetic field is weak and is aligned along the free-stream direction. The solution is sought by the method of matched asymptotic expansions under the assumptions that the magnetic pressure number b = O (1) and Rm<1, R<1.